Rituals in acculturation of islam and local traditions of the Bajo Tribe in Gorontalo - Purnama, Andi Oktami Dewi Artha Ayu; Yusuf, Andi Muhammad; Amelia, Lia; Ibrahim, Muhammad (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
This study investigates the process of assimilation of Islamic practices and indigenous customs inside the ceremonies conducted by the Bajo Tribe. The rites performed by the Bajo people encompass a fusion of Islamic tenets with their indigenous beliefs, specifically centered around their reverence for the sea's sovereign. The amalgamation of these two ideologies yields a potent synergy. The Bajo people, as Muslims, fulfill the religious obligations of Islam, which includes commemorating the birth anniversary of the Prophet Muhammad SAW. In addition, the Bajo people also perform the Massoro and Bate' rituals, which are the most significant traditional ceremonies of the Bajo Tribe in Torosiaje Village. The Bajo tribe's customs are shaped by the integration and embodiment of these two ideas, which are expressed through values, norms, and laws that serve as guiding principles for their way of life. The ceremonies performed by the Bajo people stem from established traditions passed down through generations.